Research on Vulnerability and Damage Assessment of Tactical Ballistic Missile. Issue 1 (May 2019) - Gu, Hongping; Cheng, Chun; Sun, Aixi; Lei, Xiaoyun; Shi, Yijian; Huang, Fenghua
Abstract: The threat of TBM (Tactical Ballistic Missile) on the battlefield makes it an important intercept target of anti missile system. In order to effectively evaluate the damage degree of TBM when intercepted, the system and function characteristics of TBM were analyzed with "Iskander" TBM as an example, the missile vulnerability model was constructed, the vulnerability and damage assessment program was developed, and the damage assessment test methods of TBM were summarized. The research results will help to carry out real-time evaluation of the damage effect of antimissile system towards TBM.